Assessing Environmental Awareness of Students at the University of Sulaimani - Hamaamin, Yaseen Ahmed; Abdullah, Jwan Bahadeen (Sulaimani Journal for Pure and Applied Sciences, 2018)
Rapid population growth, inadvertent economic development and urbanization led to major threats to natural resources and climate stability of our planet. Therefore, worldwide sustainable planning and management should be phased out soon to prevent environmental collapse. Hence, pro-environmental regulations and policies are crucial. The major difficulty that faces the environmental protection process, is the lack of public participation in pro-environmental behaviour. Raising the rate of environmental awareness among individuals is the effective way for improving public participation in adopting sustainable life and environment. Environmental awareness is a criterion for a harmonious living between humans and the nature. This study investigated and surveyed the environmental consciousness among the University of Sulaimani students through a five-digit scale of a questionnaire survey. In the study, randomly mixed of positive and negative prompts were used. Results of the study showed that the rate of average environmental awareness of the students was slightly above average 2.63 on a 5 digits’ scale of evaluation. Results also showed that the university commitment to environmental education is minimal,2.32 out of 5, thus, there is a gap or deficiency of required green education in most of the university colleges curriculum. This study ended with numerous suggestions to the university decision makers towards raising student’s environmental awareness. Green education can be achieved by adding environmental courses in colleges study programs, organizing seminars, and special activities regarding environmental protection.
Keywords: Students Environmental; Awareness University of Sulaimani